Die Effekte der Werbung auf unsere Gesellschaft das Körperbild der Frau - Varga Luca (2018)
THE EFFECTS OF ADVERTISING ON OUR SOCIETY: WOMEN’S BODY IMAGE Die Effekte der Werbung auf unsere Gesellschaft: das Körperbild der Frau In my thesis, I am dealing with the possible consequences of the media supported thin ide-al. Firstly, I reveal the purpose of beauty industry and the reasons why they have to sup-port the current beauty ideal. In my first assumption, I am presenting the model's represen-tation in media and commercials. Besides this, I am analysing the differences between su-per-thin models and average women. In my work I am also proving that professional mod-els physical appearance differ from average women's physical looks. I am demonstrating by empirical data and figures that the world of high fashion does not represent the reality in commercials, because only a few (real) women can fulfill the requirements of thin and beauty ideals. This world labels anorexic models as normal and average models (according to the BMI-index) as plus -size. Thereby, average women are considered rather fat than normal. My second assumption deals with the question whether supported thin ideal causes negative emotions in society and women. I have divided my research process into two parts. Firstly, I am going to examine this question based on specialized literature and dif-ferent academic researches and publications. Apart from this, I have created a special online survey which evaluates the satisfaction of the surveyed regarding their appearance and how the media and commercials affects the women's body image. Through the results of different academic researches and my own survey I have proved that significant amount of women are discontent with their body. Many women have negative emotions while looking at really attractive models in commercials. In spite of all mediacontain, Tv-shows, lying commercial campaigns and the support of thin ideal, all this can be blamed partly for the body dissatisfaction, increased body image issues, low self-estimation/confidence, attendance of eating disorder, because people consider beauty and prettiness vitally important. Many women want a faultless appearance instinctively. Hu-man nature craves for beauty. Through the results, I am pointing out that the main part of society accepts and pre-fers the current beauty and thin ideal. The mechanism of economy and various corporate objects e.g. maximising profits, increasing market shares, better position in competition all lead the economic operators to focus on their own ambitions/interests. Although the eco-nomic logic justifies the activity of the marketing departments and the marketing strategy, this process is morally problematic. Fortunately, the other part of the society does not agree with these guidelines and values. They want to show the diversity of beauty.